Taṭbīq Namūzaj at-Taʿlīm bi al-Takhmīn li Istīʿāb al-Mufradāt al-Lugah al-ʿArabiyyah laday Talamīż Rauḍah al-Aṭfāl “Nūrul Husnayain” bi Bukittinggi - Indah Sari (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
This research is about applying the guessing teaching model to comprehend the vocabulary of the Kindergarten pupils "Nurul Husnayain, Bukittinggi. The problems in this research mean that some understand the lesson, and some do not. While studying, some are dumbfounded when they hear the teacher. When reading the lessons in singing style, the pronunciation is read long but short, and vice versa. The type of research used is qualitative descriptive research. The research tools are interviews and observation. The method of data analysis used in this research is the analysis of the Millis and Huberman model, which means summarizing and exposing the data. As for the research results, there is an application of a guessing teaching model to comprehend vocabulary among pupils of Kindergarten "Nurul Husnayaian" Bukitinggi. Teaching with this model is effective to be applied in Kindergarten "TAUD NUHA." From the research results, students can answer the guesswork from the characteristics conferred by the teacher.هذا البحث عن تطبيق نموذج تعليم التخمين لاستيعاب المفردات اللغة العربية لدى تلاميذ روضة الأطفال "نور الحسنيين" ببوكيت تنجي. المشكلات في هذا البحث يعني يفهم البعض الدرس، والبعض الآخر لا أثناء الدراسة، يصاب البعض بالذهول عند الاستماع إلى المعلمة.   عند قراءة الدروس بطريقة الغناء، يقرأ النطق طويلاً ولكن مختصرًا والعكس صحيح. أما نوع البحث المستخدم هو بحث الوصفي الكيفي. وأدوات البحث هي مقابلة وملاحظة. وأسلوب تحليل البيانات الذي تستخدم الباحثة في هذا البحث هو تحليل نموذج ميليس وهوبيرمان يعني تلخيص البيانات وتعريضها. وأما نتائج البحث فهي توجد تطبيق نموذج تعليم التخمين لاستيعاب المفردات اللغة العربية لدى تلاميذ روضة الأطفال "نور الحسنيين" ببوكيت تنجي، تقوم الباحثة بتدريس نموذج تعليم التخمين باللغة العربية يتعلم التلاميذ فيه مفردات أعضاء الجسم. التعليم باستخدام هذا النموذج فعال ليتم تطبيقه في روضة الأطفال  "تود نهى" ومن نتائج البحث، يمكن للطلاب الإجابة على التخمين من الخصائص التي ينقلها المعلم.